The better the distance runner, the more slow-twitch muscle typology? - Lievens, E.; Bex, T.; Baguet, A.; Achten, E.; De Clercq, D.; Derave, W. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Classical studies on histological analyses of muscle biopsies of elite athletes have revealed that sprint-type disciplines require a predominant fast-twitch (FT) muscle fiber type composition (MFTC), whereas athletes in endurance-type disciplines thrive on largely slow-twitch (ST) muscles. However, 1) this fundamental element in exercise physiology is in present day hardly used in scientific guidance of athletes, and 2) many questions still remain unanswered regarding optimal MFTC for different sport events. Both these limitations relate to the invasive nature of the muscle biopsy, making it inapplicable in elite sports. Recently, muscle carnosine quantification by proton magnetic resonance spectroscopy (1H-MRS) was developed as a new noninvasive method to estimate MFTC (Baguet et al., 2011). By applying this technology to a large group of elite athletes, we aim to answer unresolved questions such as `Do short-distance swimmers need a predominant fast MFTC?` and `Do international-caliber distance runners have a slower MFTC than national-level runners?`. Methods: A total of 111 elite Belgian athletes (74 runners, 7 triathletes, 11 swimmers, 14 cyclists and 5 kayakers) were recruited to measure muscle carnosine content in gastrocnemius and deltoid muscle by 1H-MRS on a 3T scanner. Carnosine is a typical FT metabolite and high concentrations of carnosine correspond to a fast MFTC. Athletes were compared to a gender- and age-matched reference population (n=188). Results: Across the different sports disciplines, carnosine content showed the strongest significant correlation with cyclic movement frequency (R = 0.86, P = 0.001), though no significant correlation was found between the carnosine content and performance duration (R = -0.58, P = 0.06). Thus, swimmers -even those who compete in short events- have a more ST muscle typology than corresponding runners and cyclists. Interestingly, there was no difference in carnosine content between the international- and the national-level endurance runners (P = 0.89). The opposite was found in sprinters, as international-level athletes were characterized with higher carnosine levels than national-level athletes (P = 0.05). Discussion: Cyclic movement frequency, rather than exercise duration came out as a factor best related to the optimal estimated MFTC in elite athletes. A more extreme MFTC seems more important to excel in sprint running than in endurance running. Our findings suggest that MR-based non-invasive estimation of MFTC can have important applications in elite sports.